The Case of a Glucocorticoid-Induced Myopathy & Myasthenia Gravis Combination: Is There a Border? - Dzherieva, Irina (J Endocr Soc, 2021)
Introduction: Glucocorticoid-induced myopathy is the sign of Cushing’s syndrome in 83%, but can also be consequence of exogenous administration of glucocorticoids. The patients with the compromised neuromuscular system (for example, because of myasthenia gravis) have a higher risk of this complication. Differential diagnosis of glucocorticoid-induced myopathy is challenging. Clinical case. A 77-year woman complained of difficulty in the act of breathing, swallowing, weakness in the limbs, inability to self-service, ptosis. Due to the growing complaints the patient was hospitalized to ICU. From anamnesis: She was diagnosed with myasthenia gravis 2 months ago. The presence of autoantibodies to the nicotine acetylcholine receptor was confirmed. Pyridostigmine bromide 60 mg/day, Methylprednisolone 20 mg/day were prescribed for 5 days. The patient noted some improvement. After the next neurologist’s examination the dose of Methylprednisolone was doubled. (It is not known for certain whether the doctor wanted to reduce the dose and the patient misunderstood.) She noted some worsening: weakness and speech difficulties increased. She returned to the previous dose after 3 days, but there was no improvement. Objectively: hypersthenic body type, BMI 39 kg/m2, predominant deposition of adipose tissue in the abdomen and face. Breathing without a ventilator. BP 250/100 mm Hg, heart rate 87 BPM. Laboratory tests revealed hyperkalemia of 8.76 mmol/l (3.5–5), creatinine of 481 mmol/l (44–124), hyperglycemia of 16 mmol/l. Glucocorticoid-induced myopathy was suspected, the administration of methylprednisolone was cancelled. The improvement of the condition was noted in 3 days. Blood pressure, glycaemia, levels of potassium and creatinine returned to normal. A biopsy of muscle revealed: atrophy of type I and II muscle fibers. There were no signs of necrosis, regeneration or inflammation. Thereby the diagnosis of glucocorticoid-induced myopathy was confirmed. Conclusion. Glucocorticoid-induced myopathy may look like a decompensation of neuromuscular disease. Since there are no accurate diagnostic tests nowadays the main argument of diagnosis is the paradoxical reaction after increasing the dose of glucocorticoids as well in this case. Even a short period of use of these drugs can lead to the development of side effects. It is necessary to regularly monitor the dynamics of the condition of such patients.